Clinical utility of ultra-widefield fluorescein angiography and optical coherence tomography angiography for retinal vein occlusions - Tan, Tien-En; Ibrahim, Farah; Chandrasekaran, Priya R.; Teo, Kelvin Yi Chong (Frontiers in Medicine, 2023)
Retinal vein occlusions (RVOs) are the second most common retinal vascular disease after diabetic retinopathy, and are a significant cause of visual impairment, especially in the elderly population. RVOs result in visual loss due to macular ischemia, cystoid macular edema (CME), and complications related to neovascularization. Vascular assessment in RVOs traditionally relies on standard fluorescein angiography (FA) for assessment of macular and retinal ischemia, which aids in prognostication and guides intervention. Standard FA has significant limitations—it is time-consuming, requires invasive dye administration, allows for limited assessment of the peripheral retina, and is usually evaluated semi-qualitatively, by ophthalmologists with tertiary expertise. More recently, the introduction of ultra-widefield FA (UWF FA) and optical coherence tomography angiography (OCTA) into clinical practice has changed the tools available for vascular evaluation in RVOs. UWF FA allows for evaluation of peripheral retinal perfusion, and OCTA is non-invasive, rapidly-acquired, and provides more information on capillary perfusion. Both modalities can be used to provide more quantitative parameters related to retinal perfusion. In this article, we review the clinical utility and impact of UWF FA and OCTA in the evaluation and management of patients with RVOs.